Smac mimetics and oncolytic viruses synergize in driving anticancer T-cell responses through complementary mechanisms - Dae-Sun Kim (Nature Portfolio, 2017)
Oncolytic viruses (OV) and second mitochondrial activator of caspase (Smac)-mimetic compounds (SMC) synergistically kill cancer cells directly. Here, the authors show that SMC and OV therapies combination also synergize in vivo by promoting anticancer immunity through an increase in CD8+ T-cell response.